PENERAPAN SISTEM OSMOTIC DEHYDRATION UNTUK MENGURANGI KADAR LEMAK KERIPIK BUAH PADA PENGGORENGAN TEKANAN HAMPA UDARA - Dul Adina Adma; Kadirman Kadirman; Jamaluddin P Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2015)
The purpose of this research is to detecting the reduction of fat and moisture contents by application of osmotic dehydration system and acceptable concentration from the using calcium chloride (CaCl2) and also the connection between the content of water with oil absorption. This research is conducted with the experimental method by using Completely Randomized Design (CRD) for detecting the effect from the four concentrations of calcium chloride (CaCl2) are  0.5%, 1.0%, 1.5%, and 2.0%  also with the control that do not contain CaCl2 by using vacuum pressure fryer. The observation of fat content is done after frying and the moisture content is done before and after frying. The result of the research is analyzed by analysis of variance and continuing by using testing HSD (Honestly Significant Difference) at 5%. The results shows that the reduction in the lowest fat content is detected in the concentration of  0,5% CaCl2 but for the moisture content does not have a significant influence